Analisis Model Indeks Zakat Nasional Untuk Menilai Kinerja Zakat (Studi Kasus Baznas Kabupaten Solok Sumatera Barat Tahun 2020) - Annisa Maulidia Alfian; Arif Pujiyono; Alfian Alfian (Universitas Islam Lamongan, 2022)
This research aims at measuring BAZNAS Solok Regency performance in order to evaluate and improve performance in managing zakat. The potential of Zakat in Solok Regency is very large, but the process of collecting zakat carried out by BAZNAS Solok Regency has not been maximized. This problem is because of the low-level of public trust in distributing zakat to institutions. The public trust will increase if the institution performs the reliable and credible performance. Data collection methods is accomplished through interviews and questionnaires. The analysis method uses the National Zakat Index (NZI) and Instrument Test which includes validity test, reliability test and paired test. The results of the BAZNAS Solok Regency research from the macro dimension are quite good with an index value of 0.50, as there is no APBD support from Solok Regency government and the zakat institution database is not completed yet. From the micro dimension, the performance assessment of BAZNAS Solok Regency is good with an index value of 0.61, as well as the value of institutional indicators including collection, management, delivery and reporting that turns out well. Yet, the impact of the zakat given needs such further reevaluation, because BAZNAS Solok Regency has not carried out guidance, monitoring and evaluation on the material side and spiritual mustahik.